Changes in self-reported and accelerometer-based sleep during the transition to retirement - Myllyntausta, Saana (fi=Turun yliopisto|en=University of Turku|, 2020)
This study aimed at examining how different characteristics of sleep change during transition from full-time work to statutory retirement. Changes in sleep were examined among public sector employees in Finland using data from two longitudinal cohorts, the Finnish Public Sector (FPS) study and the Finnish Retirement and Aging (FIREA) study. Sleep was measured with self-reports and wrist-worn accelerometers up to 6 years before and 6 years after retirement. Changes in sleep duration, different types of sleep difficulties, daytime tiredness, and sleep loss due to worry, as well as in the timing of sleep, time spent in bed, and sleep efficiency were examined. Furthermore, information on different pre-retirement sociodemographic, work, and health factors was obtained and changes in sleep were examined in relation to these different pre-retirement characteristics. During the transition to retirement, sleep duration increased by approximately 22 minutes (ranging from 19 minutes to 25 minutes depending on the measurement interval around retirement and the sleep measure that was used). The prevalence of sleep difficulties decreased during the retirement transition and particularly the prevalence estimates of waking up too early in the morning and nonrestorative sleep were observed to decrease. Decreases were observed also in the prevalence of daytime tiredness and sleep loss due to worry. Compared to working days prior to retirement, both in bed and out bed times were delayed, and thus, retirement was associated with a later sleep-wake rhythm. Factors associated with the sleep changes during the retirement transition were identified, including short sleep duration, job strain, and psychological distress prior to retirement. In conclusion, statutory retirement is associated with longer sleep duration and less sleep difficulties for many retirees retiring from public sector work. As there seems to be more inadequate sleep, sleep difficulties, and daytime tiredness during the final working years than after retirement, this study also highlights the importance of promoting sleep health of older employees.

Tämän tutkimuksen tavoitteena oli selvittää, kuinka unen eri osa-alueet muuttuvat siirryttäessä kokoaikaisesta työstä ikäperusteiselle eläkkeelle. Unen muutoksia tutkittiin suomalaisilla kunta-alan työntekijöillä käyttäen Kunta10- ja Sairaalahenkilöstön hyvinvointitutkimuksen sekä Aktiivisena eläkkeelle -tutkimuksen pitkittäisaineistoja. Unta mitattiin sekä kyselyillä että ranteessa pidettävällä liikemittarilla. Tutkimuksessa selvitettiin muutoksia itsearvioidussa ja liikemittariin pohjautuvassa unen kestossa, erityyppisissä univaikeuksissa, päiväaikaisessa väsyneisyydessä ja huolien vuoksi valvomisessa sekä myös unen ajoituksessa, sängyssä vietetyssä ajassa ja unen tehokkuudessa. Tutkimuksessa tarkasteltiin myös, miten eläköitymistä edeltävät sosiodemografiset ja työhön sekä terveyteen liittyvät tekijät ovat yhteydessä unessa havaittuihin muutoksiin. Eläkkeelle siirryttäessä unen kesto lisääntyi keskimäärin noin 22 minuutilla (vaihdellen 19 minuutista 25 minuuttiin riippuen mittausaikavälistä eläköitymisen ympärillä sekä käytetystä mittausmenetelmästä). Univaikeuksien esiintyvyys väheni eläköitymisen jälkeen ja erityisesti vähenivät liian aikaiset aamuheräämiset ja virkistämätön uni. Myös huolien vuoksi valvomisen ja päiväaikaisen väsyneisyyden havaittiin vähenevän. Eläköitymisen myötä uni-valverytmi siirtyi myöhäisemmäksi, sillä sekä nukkumaanmeno- että heräämisajat olivat eläköitymisen jälkeen myöhempiä kuin työpäivinä ennen eläköitymistä. Eläköitymistä edeltävistä tekijöistä lyhyt unen kesto, työn kuormittavuus ja heikko itsearvioitu terveys ennen eläköitymistä olivat yhteydessä unessa tapahtuviin muutoksiin eläköidyttäessä. Tämän tutkimuksen tulokset osoittavat, että ikäperusteinen eläköityminen tarkoittaa monille muutosta kohti pidempää yöunta ja univaikeuksien vähentymistä. Tutkimus myös korostaa ikääntyneiden työntekijöiden riittävän ja hyvänlaatuisen unen tukemisen tärkeyttä osoittaessaan, että riittämätön uni, univaikeudet ja päiväaikainen väsymys ovat yleisempiä viimeisien työvuosien aikana kuin eläkkeellä.